Function by Structure: Spotlights on Xist Long Non-coding RNA - Pintacuda, Greta; Young, Alexander N.; Cerase, Andrea (Frontiers in Molecular Biosciences, 2017)
Recent experimental evidence indicates that lncRNAs can act as regulatory molecules in the context of development and disease. Xist, the master regulator of X chromosome inactivation, is a classic example of how lncRNAs can exert multi-layered and fine-tuned regulatory functions, by acting as a molecular scaffold for recruitment of distinct protein factors. In this review, we discuss the methodologies employed to define Xist RNA structures and the tight interplay between structural conservation and functionality of lncRNAs. This model of modular function dictated by structure, can be also generalised to other lncRNAs, beyond the field of X chromosome inactivation, to explain common features of similarly folded RNAs.